Raw pollen counts of MIS 31 from IODP Site 339-U1385, SW Iberian margin - Dulce Oliveira; Maria Fernanda Sanchez Goñi; Filipa Naughton; Josué M Polanco-Martínez; Francisco J Jimenez-Espejo; Joan O Grimalt; Belén Martrat; Antje H L Voelker; Ricardo M Trigo; David A Hodell; Fatima F Abrantes; Stéphanie Desprat (PANGAEA, 2025)
Raw counts of identified pollen and spores IODP Site 339-U1385, SW Iberian margin, for the early Pleistocene interval MIS 32-30 (1,100-1,050 ka)
In: Oliveira, D et al. (2025): Deep-sea pollen record of MIS 31 from IODP Site 339-U1385, SW Iberian margin [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986770